Exploration of historical Malacca: through the use of 3D game simulation for the learning of history subject for KBSM / Amir Shariffuddin Zakaria - Zakaria, Amir Shariffuddin (2010)
The history subject had been observed as a boring subject to almost every student in this world. Having to read and just listening to the teacher's teaching is not interesting and the student is also passive. The objective of study is to investigate the potential of the 3D game simulation as to supplement the traditional teaching method and to generate student interest in learning of history subject for KBSM. The potential of the computer games and simulation has not been embedded into the mainstream education. Even though there are many computer games being developed for education but mainly focus into commercial aspect and did not really engaged with educators. With leading-edge technologies and the rapid deployment of computer games engine could lead to new learning pedagogies in education especially to the history subject. This is because 3D game simulation have the ability to empower the learning process to the student as it could provide substantial impact to history subject by allowing the student to discovery, exploration and evaluate the data, by personally experiencing the events virtually. This could help the student to generate further understanding of historical event. The research findings supports the hypothesis that the use of 3D game simulation format for history subject could stimulate physical response to the player or student as many had claimed that they feel immersed into the virtual world when playing the game. Result from the experiment proves that computer games can provides a significant learning advantage to the student and helps to arouse the students interest to learn history subject.